Risk assessment and simulation optimization of evacuation in large public building fires: A case study - Qiang Li; Zaohong Zhou; Yunbin Sun; Hongjun He (Progress in Disaster Science)
Fires in large public buildings cause substantial losses. Conducting reasonable evacuation risk assessments and simulation studies for early warning is essential. A comprehensive fire evacuation risk assessment model is proposed, consisting of a fire evacuation risk assessment framework based on Pythagorean fuzzy sets(PFS) and fuzzy comprehensive evaluation(FCE) and fire evacuation simulations. The fire evacuation risk assessment is conducted using PFS and FCE. Simulations with BIM, Pyrosim, and Pathfinder validate the results through dynamic safety analysis. This innovative approach enhances the dynamic safety analysis of evacuations. Additionally, the study improves the integration between Pyrosim and Pathfinder software, providing more accurate and reliable simulation results. Taking a cafeteria for primary and secondary school students as an example, the results indicate that the fire evacuation risk level of the student cafeteria is “moderately high risk.” Visibility is found to be the most critical factor affecting available safe evacuation time, compared to CO concentration, smoke layer height, and temperature. Not all cafeteria occupants could evacuate within the preset time, and significant congestion was observed. Thus, the assessment results are deemed reliable. Based on these results, targeted fire safety evacuation control strategies are proposed to enhance the efficiency and safety of evacuations in similar venues.